Investigation on Phytochemical Constituents and Antimicrobial Activity of Methanolic Extract of Sonneratia apetala Buch-Ham. Areal Parts - Sangram Keshari Panda; Debasis Pati; S. K. Mishra; S. Sahu; B. Tripathy; L. Nayak (Technological Innovation in Pharmaceutical Research Vol. 3, 2021)
The aim of this study was to look into the phytochemical constituents and antimicrobial activity of Sonneratia apetala arial parts methanolic extracts. Terpenoid, steroid, alkaloid, flavonoid, tannins, saponins, and polysaccharide were contained in the phytochemical constituents of methanolic extracts of S. apetal. The well diffusion method was used to assess the antimicrobial activities of the plant extracts. The tested extract had antibacterial activity against both gram-negative and gram-positive bacteria to varying degrees. These positive results indicate that the plant material has antibacterial properties. In comparison to standard anti-microbial agents ciprofloxacin and clotrimazol at 10 g/disc, the anti-microbial activity of the methanolic extract of S. apetala at 10 mg/ml was found to be dose dependent and meaningful.